Clive Barker's Lord of illusions [videorecording (DVD)] - Boswell, Simon (Metro-Goldwyn-Mayer Studios Inc., 2024)
A detective gets more than he bargained for when he meets a dangerous illusionist. He's thrust into a nightmare of murder, deception and terrifying assaults from the dark beyond. Documentary of Clive Barker.